PENGEMBANGAN BAWANG GORENG DALAM KEMASAN By DAPOER SAHNAYA (STUDI DENGAN PENDEKATAN RENCANA BISNIS) - Yudha Aditya Ramadhana; Idris Idris (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT The Business Plan for the Bawang Goreng By Dapoer Sahnaya business was created to analyze the Bawang Goreng By Dapoer Sahnaya business, so that the owner of the Bawang Goreng By Dapoer Sahnaya can find out whether the business is feasible or not feasible to run. Some of the analyzes used include financial aspects, market and marketing aspects, management aspects, HR aspects, operational aspects, environmental, social and cultural aspects and legal aspects. Financial aspect focuses on financial sensitivity analysis which includes Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period and B/C ratio. In running a business Bawang Goreng By Dapoer Sahnaya, it requires funds of Rp 245,735,018 consisting of Rp 199,194,718 own funds and credit capital of Rp 46,450,300. The results of research conducted using normal sensitivity analysis with the results of the Net Present Value (NPV) of Rp 437.212.437, Internal Rate of Return (IRR) of 53%, Payback Period (PBP) for 2 years 7 months and benefit and cost ratio (B/C Ratio) of 1,88. With the calculation of sensitivity analysis, Bawang Goreng By Dapoer Sahnaya business can be said to be feasible to run and can survive the conditions that will exist in the future